2005
DOI: 10.1111/j.1744-1617.2005.00006.x
|View full text |Cite
|
Sign up to set email alerts
|

THE COLLABORATIVE DIVORCE PROJECT: 
A Court‐Based Intervention for Separating Parents with Young Children

Abstract: The role the legal process of separation and divorce plays in affecting outcomes for young children and their families was examined in the Collaborative Divorce Project (CDP), an intervention designed to assist the parents of children six years old or younger as they begin the separation /divorce process (married and unmarried couples). Evaluation and outcome data were collected from 161 couples, their attorneys, teachers, and court records. In addition to positive evaluations from both parents, intervention f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 24 publications
0
58
0
1
Order By: Relevance
“…Cowan et al relationship between the parents, especially in their reciprocal exchange of negative emotions as they try to resolve differences between them (Katz & Gottman, 1993) or as they work and play together with their child as co-parents (McHale, Khazan, Erera, Rotman, DeCourcey, & McConnell, 2002). The extensive research literature on marital quality, parent-child relationship quality, and children's adaptation has been summarized by a number of authors who find that high, unresolved marital conflict between parents is associated with negative indicators of development in their children and adolescents (Cowan & Cowan, 2006;Cox, Paley, & Harter, 2001;Cummings & Davies, 1994;McHale, Kazali, Rotman, Talbot, Carleton, & Lieberson, 2004;Pruett, Insabella, & Gustafson, 2005). Furthermore, there is strong support for a spillover hypothesis: that marital difficulties tend to color the quality of the relationship between each parent and the child (Lindahl, Clements, & Markman, 1997, p. 385).…”
Section: Template Models That Link Attachment In Parents and Childrenmentioning
confidence: 99%
“…Cowan et al relationship between the parents, especially in their reciprocal exchange of negative emotions as they try to resolve differences between them (Katz & Gottman, 1993) or as they work and play together with their child as co-parents (McHale, Khazan, Erera, Rotman, DeCourcey, & McConnell, 2002). The extensive research literature on marital quality, parent-child relationship quality, and children's adaptation has been summarized by a number of authors who find that high, unresolved marital conflict between parents is associated with negative indicators of development in their children and adolescents (Cowan & Cowan, 2006;Cox, Paley, & Harter, 2001;Cummings & Davies, 1994;McHale, Kazali, Rotman, Talbot, Carleton, & Lieberson, 2004;Pruett, Insabella, & Gustafson, 2005). Furthermore, there is strong support for a spillover hypothesis: that marital difficulties tend to color the quality of the relationship between each parent and the child (Lindahl, Clements, & Markman, 1997, p. 385).…”
Section: Template Models That Link Attachment In Parents and Childrenmentioning
confidence: 99%
“…Four programs had a core focus on conflict within the interparental relationship (see text box), all of which originated from the United States. Evidence from RCTs indicated positive effects, reducing interparental conflict, as well as indicating improvements in child outcomes (Dads for Life, DfL, Cookston, Braver, Griffin, De Luse, & Miles, ; Collaborative Divorce Project, CDP, Pruett, Insabella, & Gustafson, ; Kids in Divorce & Separation, K.I.D.S., Shifflett & Cummings, ; Mentalization, Hertzmann et al., ) with small to moderate effect sizes (where possible to estimate). Three programs were also identified that had a parenting focus with a couple component in the context of divorce/separation (see Table for details).…”
Section: Improving Outcomes For Children Who Experience Acrimonious Imentioning
confidence: 99%
“…This general conclusion also applies to families in which parents are in the process of divorce. In Pruett and Barker's () review of postdivorce interventions with mothers or fathers, or in one study with an intervention for both divorcing partners (M. K. Pruett, Insabella, & Gustafson, ), parents' participation resulted in reduced conflict between the parents and improved outcomes for children.…”
Section: Implications Of Correlational Research For Family‐based Intementioning
confidence: 99%